Materials selection in mechanical design - Ashby, Michael F., 1935- (Oxford Butterworth-Heinemann, 2010)
Understanding materials, their properties and behavior is fundamental to engineering design, and a key application of materials science. Written for all students of engineering, this book describes the procedures for material selection in mechanical design.
Incluye bibliografía por capítulos e índice
Keywords: Materiales; Ingeniería del diseño